Peningkatan Hasil Belajar PKn melalui Pembelajaran Aktif Giving Question and Getting Answer pada Siswa kelas V A SD Inpres Tetebatu Kabupaten Gowa (JED (Jurnal Etika Demokrasi), 2017)
This study aims to improve the learning outcomes of Civics through the application of learning models Active Giving Question and Getting Answer on Grade V Students of Primary School Inpres Tetebatu Gowa Regency. This research is a kind of descriptive class action research that is qualitative and descriptive statistic that is quantitative. The subjects of the study were the students of Grade V A of Elementary School of Inpres Tetebatu of Gowa Regency amounting to 39 people. This research was conducted in two cycles consisting of four components namely planning, action, observation / observation, and reflection. Data collection techniques used are the provision of tests and observations. The data obtained were analyzed qualitatively and quantitatively. Result of research: (1) Student learning achievement improvement on Civic subject through Active Learning Model Giving Question and Getting Answer to Grade V student of Primary School of Inpres of Tetebatu Gowa Regency. This can be seen from the cycle I that completeness of learning only reached 72% with an average of 73.52 and then rose to 87% in cycle II with an average of 81.28. (2) Application of Active Learning Model Giving Question and Getting Answer can improve the learning result of Civics in class V A Primary School of Inpres Tetebatu Gowa Regency South Sulawesi Province.Keywords: Learning Outcomes, Giving Question and Getting Answer